Critical point for the Deformation Dependent Mass model through a variational procedure - Petrellis, D. (HNPS Advances in Nuclear Physics, 2019)
The recently introduced Deformation-Dependent Mass model is combined with a variational approach to the Bohr Hamiltonian in order to describe transitional nuclei. The results of this procedure are demon- strated for the ‘spherical to γ-unstable’ and the ‘spherical to deformed’ transitional classes, which corre- spond to the E(5) and X(5) solutions.